A Meta-Analysis on the Efficacy and Safety of Bacterial Lysates in Chronic Obstructive Pulmonary Disease - Huang, Yongkang; Pei, Yongjian; Qian, Yajuan; Yao, Zhen; Chen, Chen; Du, Juan; Shi, Minhua; Zhou, Tong (Frontiers in Medicine, 2022)
Background Chronic obstructive pulmonary disease (COPD) is a common and frequently encountered disease of respiratory apparatus and is vulnerable to infection. Increasing studies reveal that bacterial lysates play an encouraging role in preventing exacerbations in these patients. We here investigated the efficacy and safety of bacterial lysates in COPD. Methods We performed systematic research on PubMed, EMBASE, the Cochrane Library (CENTRAL), and Web of Science by using the keywords and their synonyms for studies published before January 11, 2022. Two researchers screened the studies of literature independently according to the inclusion and exclusion criteria and extracted data from the included studies. Another two researchers assessed the risk of bias of each included using the Cochrane risk-of-bias tool. Meta-analysis was conducted using R (version 4.1.1, The R Foundation for Statistical Computing) and Review Manager (version 5.4.0, The Cochrane Collaboration). Results A total of 12 studies were included in this meta-analysis, and the pooled results showed that bacterial lysates were effective to reduce exacerbation rate (overall: relative risk [RR] = 0.83, 95% confidence interval [CI] 0.72–0.96; alkaline bacterial lysate subgroup [OM-85]: RR = 0.87, 95% CI 0.77–0.98; mechanical bacterial lysate subgroup [Ismigen]: RR = 0.70, 95% CI 0.41–1.20) and mean number of exacerbations (overall: MD = −0.42, 95% CI −0.75 to −0.08; alkaline bacterial lysate subgroup [OM-85]: MD = −0.72, 95% CI −1.35 to −0.09; mechanical bacterial lysate subgroup [Ismigen]: MD = −0.02, 95% CI −0.21 to 0.17). Bacterial lysates were also found beneficial in alleviating symptoms. The side effects were acceptable and slight. Conclusion Bacterial lysates can benefit patients with COPD by reducing exacerbations and alleviating symptoms. OM-85 is the preferable product based on the existing evidence. Further studies are needed to validate these findings. Systematic Review Registration [www.crd.york.ac.uk/prospero/], identifier [CRD42022299420].